Communicating dynamic behaviors in basketball: The role of verbal instructions and arrow symbols - Khacharem, A.; Trabelsi, K.; Zoudji, B.; Kalyuga, S. (Research Quarterly for Exercise and Sport, 2020)
Purpose: Guided by cognitive load theory and cognitive theory of multimedia learning, the purpose of this study was to evaluate players' ability to integrate dynamic information presented under different conditions: a verbal condition, in which instructions were given orally; a visual condition, in which instructions were shown using arrow symbols; and a redundant condition, in which both visual and verbal instructions were presented simultaneously. Method: In a 2 × 3 design, we asked basketball players with varied levels of skill (less-skilled, skilled) to rate their invested mental effort and to perform a recall test after learning from either the verbal, visual or redundant condition. Results: Results demonstrated that the less-skilled players benefited more from the redundant condition, whereas the skilled participants benefited more from the visual condition. Conclusion: Recommendations for improving instructional design techniques aimed at the transmission of tactical instructions in team games are proposed.